A double-stranded DNA catalyzed strand displacement system for detection of small genetic variations. Issue 92 (3rd November 2020) - Liu, Na; Zhang, Xuzhe; Tang, Xiaofeng; Liu, Yizhou; Huang, Donghui; Xiao, Xianjin
Abstract : A double-stranded DNA catalyzed strand displacement system was established for the detection of small genetic variations. Abstract : A double-stranded DNA catalyzed strand displacement system (dsCSD) was established for the detection of small genetic variations, which showed greatly enhanced specificity compared to the conventional single-stranded DNA catalyzed strand displacement (ssCSD) system. The system achieved limits of detection (LODs) of 0.05% and 0.1% for synthesized DNA samples and clinical gene samples, respectively.